Relação entre risco, trabalho e meio ambiente para os profissionais de enfermagem - Diaz, Paola da Silva (2013)
When we think of the hospital context in which nursing staff are inserted, especially when considering that they are in contact with some risk situations present in this scenario as well as the "products" resulting from actions necessary to perform nursing care, many questions can be explored. One is related to the quest for understanding that nursing workers, inserted in this context, have about risk and correlations that this may have on health and the environment. In this sense the goals of this study were: to know what the nursing staff working in the hospital context mean by risk; highlight the perception of nursing workers about exposure to risks in the context of hospital work, and understand the perceptions of nursing staff on the interface environment and risk. The investigation is classified as descriptive and exploratory, qualitative approach and was conducted with nursing staff of a university hospital in southern Brazil Data collection occurred through 13 semi-structured interviews with leading questions about the topic investigated, and non-participant observation. Data were collected during the months from May to September 2012 and analyzed based on the proposed benchmark for content analysis. To meet the ethical was fulfilled in full resolution 196/96. The results are presented in three articles. The first article is organized into two categories: risk: a concept vague and imprecise, and a narrow definition of risk. The second article is composed by categories: risks related to the profession, the relevance of chemical and biological hazards, ergonomic risk and psychological risk limitations proper use of Personal Protective Equipment. Finally, the third article consists of the categories: risk and environment: another story; Risk and environment: the issue of waste, and the responsibility of nursing risk facing interface and environment. Given the findings, it reinforces the idea that in the case of risks, there is still much to advance in terms of spreading knowledge and ownership on the subject. What denotes something that should be carefully attempt by nursing staff, since they have a stake and role in various issues that involve risks, both for the health of workers, and for patients assisted by them and for the environment.